Regenerative Strategies for Craniofacial Disorders - Garland, Catharine B.; Pomerantz, Jason H. (Frontiers in Physiology, 2012)
Craniofacial disorders present markedly complicated problems in reconstruction because of the complex interactions of the multiple, simultaneously affected tissues. Regenerative medicine holds promise for new strategies to improve treatment of these disorders. This review addresses current areas of unmet need in craniofacial reconstruction and emphasizes how craniofacial tissues differ from their analogs elsewhere in the body. We present a problem-based approach to illustrate current treatment strategies for various craniofacial disorders, to highlight areas of need, and to suggest regenerative strategies for craniofacial bone, fat, muscle, nerve, and skin. For some tissues, current approaches offer excellent reconstructive solutions using autologous tissue or prosthetic materials. Thus, new “regenerative” approaches would need to offer major advantages in order to be adopted. In other tissues, the unmet need is great, and we suggest the greatest regenerative need is for muscle, skin, and nerve. The advent of composite facial tissue transplantation and the development of regenerative medicine are each likely to add important new paradigms to our treatment of craniofacial disorders.